A newsmaker's tool: The 35mm camera and journalism's material epistemology. (October 2017) - Creech, Brian
As devices become a more visible and integral part of media practice, it is important for researchers and scholars to attend to the ways in which philosophies, professional discourses, and technical limits structure the ways these technologies are deployed. The 35mm camera is a technological waypoint between earlier large-format cameras and contemporary digital photography and offers a useful historical example for interrogating the relationship between seemingly inert technical operations and journalism's modes of meaning production. To that end, this article offers a theoretical perspective for interrogating the 35mm camera through the lens of Latour, with the aim of developing a schema for integrating devices into the cultural study of media and communication.